(untitled) (Indus Journal of Bioscience Research, 2025)
Acute Myocardial Infarction (AMI) continues to be a leading cause of mortality worldwide. The standard treatment involves prompt management with Primary Percutaneous Coronary Intervention (PPCI); however, the optimal duration of hospital stay following PPCI remains an area of ongoing investigation. This study aimed to assess the safety and outcomes associated with very early discharge (VED) in patients after uncomplicated PPCI. This prospective observational study included 148 STEMI patients treated at a leading cardiac center in Lahore, Pakistan, from August 2022 to August 2023. Participants were categorized into two groups: those discharged within 24 hours (very early discharge group) and those discharged between 24 and 48 hours (early discharge group) post-PPCI. Baseline characteristics, procedural details, and early outcomes were documented. The primary outcomes were Major Adverse Cardiac and Cerebrovascular Events (MACCE) at 7-day and 30-day follow-ups. Data analysis was performed using Student’s t-tests, Chi-square tests, and logistic regression. A p-value of ≤0.05 was deemed statistically significant. The primary outcomes were assessed as Major Adverse Cardiac and Cerebrovascular Events (MACCE) at 7-day and 30-day follow-ups. The study found no significant differences in MACCE rates between the very early discharge group (5.43% at 7 days and 10.8% at 30 days) and the early discharge group (5.35% at 7 days and 10.7% at 30 days), with p-values of 0.98 and 0.97, respectively. VED criteria included successful PCI, LVEF ≥ 40%, and no major in-hospital complications. The discharge of low-risk patients within 24 hours after uncomplicated PPCI was found to be safe and feasible and indeed an effective strategy to improve bed utilization and reduce healthcare cost without increasing the risk for adverse outcome.